Changes in Deadwood and Understory Vegetation 12 Years after Partial and Clearcut Harvesting in Mixedwood Stands of Western Quebec, Canada. Issue 3 (9th March 2020) - Maleki, Kobra; Lafleur, Benoit; Harvey, Brian D; Mazerolle, Marc J; Fenton, Nicole J
Abstract: Ecosystem management promotes the integration of knowledge of natural ecosystem dynamics into forest-management planning and practices, and provides a useful framework for understanding and mitigating the impacts of timber harvesting on biodiversity and ecosystem functions. Understory vegetation and deadwood are involved in many ecosystem functions including nutrient and carbon, and tree-regeneration dynamics. The study objective was to compare the 12-year post-treatment effects on forest floor attributes of two intensities of partial harvesting (gap harvesting [62 percent basal area retention; BAR] and diameter-limit harvesting [35 percent BAR]) to clearcutting (10 percent BAR). We quantified the standing and downed deadwood abundance and the understory plant community composition in mixed, northern temperate forests, in western Québec, Canada. Our results suggest that moderate-intensity gap harvesting can best preserve a standing deadwood stem density and a diameter structure comparable to unmanaged stands. Downed deadwood abundance of all diameter classes was not altered, 12 years following the gap harvesting. Finally, understory plant communities in the gap treatment were more similar to those of unmanaged stands than those in diameter-limit and clearcutting treatments. These results illustrate the importance of tree retention levels for the maintenance of deadwood and understory plant species associated with closed-canopy or old-growth forests.